Mechanism and Origins of Regioselectivity of Copper-Catalyzed Borocyanation of 2‑Aryl-Substituted 1,3-Dienes: A Computational Study - Li, Xiaojie; Wu, Hongli; Wu, Zhenzhen; Huang, Genping (Journal of organic chemistry, 2019)
Density functional theory calculations were performed to investigate the copper-catalyzed borocyanation of 2-aryl-substituted 1,3-dienes. The computations show that the regioselectivity of the overall reaction is governed by the combination of the inherent regioselectivity of the borocupration and electrophilic cyanation steps. The π-conjugation effect of the 1,3-diene makes the terminal carbon atoms more electrophilic compared with the internal carbon atoms, which coupled with the steric effect results in the 4,3- and 1,2-borocupration being intrinsically more favorable than the other possibilities. The steric repulsion around the breaking Cu–C bond was found to be the key factor in determining the regioselectivity of the electrophilic cyanation. The origins of the experimentally observed ligand-controlled regioselectivity were ascribed to the electronic and steric effects. For the bulky XantPhos ligand, the 4,3-borocupration was found to be more favorable than the 1,2-borocupration due to the steric repulsion around the forming Cu–C bond, resulting in the formation of the 4,3-borocyantion product. On the other hand, the reversed regioselectivity with a small PCy3 ligand is mainly caused by the electronic effect that the π-electron-withdrawing aryl group at the C2 atom makes the C1 atom more electrophilic than the C4 atom, enabling the 1,2-borocupration to be more favorable than the 4,3-borocupration.